"How Do Those Danish Bastards Sleep at Night?"*: Fan Labor and the Power of Cuteness. Issue 7 (November 2018) - Goggin, Joyce
This article considers LEGO's fans and how their labor was mobilized to create The LEGO Movie . Many aspects of this film make it a compelling case study for ludic economies, such as the film's self-conscious humor that suggests an awareness on of the company's brand-growing strategies. My argument will address fans' response to how LEGO has farmed their labor and the lack of resistance encountered in the extraction thereof. I will suggest explanations as to why this is the case, including the kinds of affect generated by LEGO and LEGO narratives as they are transmediated across platforms, from bricks, to animation shorts, to The LEGO Movie . This investigation will include a discussion of LEGO's staying power in light of one particular aesthetic—cuteness—that contributes to the affective bonds people form with the bricks and the impact of this bond on consumer subjectivities.